Communication and Quality Assurance: experience of the School of Nursing of the University of Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2023)
This research reconstructs the process and experiences of collaborative work between the School of Nursing Information and Dissemination Commission and the advisers of the Center for Academic Evaluation of the University of Costa Rica, during the design and execution of the Strategic Plan of Communication in the period of 2021-2022, as part of the intrinsic elements of Quality Management. The objective of this systematization of experiences was to reflect on the strategies proposed and the learnings obtained from the process. For this, the methodological proposal of Jara (2012) was used. For the analysis of the experience, minutes of meetings, official records, and other documents derived from collaborative work were used. Communication planning facilitates and strengthens the achievement of the objectives related to the quality management of Higher Education, since it is a transforming element that optimizes processes, favors accountability, and generates community among the people involved.
Keywords: Communication process; Educational quality